Control of Mycobacterium fortuitum and Mycobacterium intracellulare infections with respect to distinct granuloma formations in livers of BALB/c mice - Tânia Regina Marques da Silva; Antonio Luis de Oliveira Almeida Petersen; Theo de Araújo Santos; Taís Fontoura de Almeida; Luiz Antônio Rodrigues de Freitas; Patrícia Sampaio Tavares Veras (Memorias do Instituto Oswaldo Cruz, 2010)
Mycobacterium fortuitum is a rapidly growing nontuberculous Mycobacterium that can cause a range of diseases in humans. Complications from M. fortuitum infection have been associated with numerous surgical procedures. A protective immune response against pathogenic mycobacterial infections is dependent on the granuloma formation. Within the granuloma, the macrophage effector response can inhibit bacterial replication and mediate the intracellular killing of bacteria. The granulomatous responses of BALB/c mice to rapidly and slowly growing mycobacteria were assessed in vivo and the bacterial loads in spleens and livers from M. fortuitum and Mycobacterium intracellulare-infected mice, as well as the number and size of granulomas in liver sections, were quantified. Bacterial loads were found to be approximately two times lower in M. fortuitum-infected mice than in M. intracellulare-infected mice and M. fortuitum-infected mice presented fewer granulomas compared to M. intracellulare-infected mice. These granulomas were characterized by the presence of Mac-1+ and CD4+ cells. Additionally, IFN-γmRNA expression was higher in the livers of M. fortuitum-infected mice than in those of M. intracellulare-infected mice. These data clearly show that mice are more capable of controlling an infection with M. fortuitum than M. intracellulare. This capacity is likely related to distinct granuloma formations in mice infected with M. fortuitum but not with M. intracellulare.